DIAMOND: A tool for monitoring the participation of students in online lectures - Mershad, Khaleel (2022)
The principle of traditional education has transformed fundamentally within the last few years. The growth of new computer and communication technologies has provided learners with access to a variety of quality online education. Many educational institutions have shifted partially or completely to distance learning and online lectures as their major instruction methods. With these new models, various difficulties related to classroom management and students’ monitoring during online lectures face many instructors worldwide. In addition, educational administrators, such as school principals and university deans, find it very difficult to assure that students are participating and actively engaging during online lectures. In this paper, we present a framework that can be utilized to monitor online lectures and deduce important figures, such as the degree of students’ involvement, the percentage of students who are participating, and the amount of engagement of each student during each lecture. The proposed system analyzes the recorded lectures and performs voice diarization on the audio signals to produce the required outputs. The system was tested during five online courses in multiple majors. The results illustrate the importance of monitoring the online lectures of distance learning courses to ensure satisfactory students’ participation.